Preliminary study of radio astronomical lines effect of rain below 2.9 GHZ - Umar, R.; Sabri, N.H.; Abidin, Z.Z.; Ibrahim, Z.A.; Azid, A.; Juahir, H.; Toriman, M.E.; Kamarudin, M.K.A. (Penerbit UTM Press, 2015)
An appropriate site selection for radio astronomy observation is very important in order to find a low level site in RFI value. The aim of this study is to select the best possible factors for astronomical observation sites. There are many factors such as slope, raindrop, river, population density, road network, land used, wireless telephone technology interrupts radio astronomy observation. In this study, we have reported one of the factors that affect radio observation which is rain effect. The site selection study is the most crucial part of decision makers proposes where to build an astronomical observatory, especially in radio astronomy with a maximum efficiency. The observation apparatus was set up to study the effect of rainfall and raindrop to the radio signal. We found that, in the inside observation, we found that spectral lines (Deuterium, Hydrogen, and two Hydroxyl lines) show that the rain gives no effect to radio signal in those windows. We also found that there is very small fluctuate value are very small (about -2 dB) for outside observation. It can be considered has no significant effect on rain below 2.9 GHz.